Spared nerve injury model to study orofacial pain - Daniel Pozza (2016)
Background & objectives: There are many difficulties in generating and testing orofacial pain in animal models. Thus, only a few and limited models that mimic the human condition are available. The aim of the present research was to develop a new model of trigeminal pain by using a spared nerve injury (SNI) surgical approach in the rat face (SNI-face). Methods: Under anaesthesia, a small incision was made in the infraorbital region of adult male Wistar rats. Three of the main infraorbital nerve branches were tightly ligated and a 2 mm segment distal to the ligation was resected. Control rats were sham-operated by exposing the nerves. Chemical hyperalgesia was evaluated 15 days after the surgery by analyzing the time spent in face grooming activity and the number of head withdrawals in response to the orofacial formalin test. Results: SNI-face rats presented a significant increase of the formalin-induced pain-related behaviours evaluated both in the acute and tonic phases (expected biphasic pattern), in comparison to sham controls. Interpretation & conclusions: The SNI-face model in the rat appears to be a valid approach to evaluate experimental trigeminal pain. Ongoing studies will test the usefulness of this model to evaluate therapeutic strategies for the treatment of orofacial pain.